Simple Method for Detection of Penicillinase-Producing Neisseria gonorrhoeae - Hodge, Wavell (1978)
A simple, reliable, and economical method for detection of penicillinase-producing Neisseria gonorrhoeae using a penicillin disk and a penicillin-sensitive organism is described.